2006
DOI: 10.1590/s0066-782x2006000600002
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[Additional cardiovascular risk factors associated with excess weigth in children and adolescents: the Belo Horizonte heart study]]>

Abstract: OBJECTIVETo examine the association of overweight and obesity with physical activity, blood pressure (BP) and serum lipid profi les. METHODSEpidemiologic investigation of 1,450 students, between the ages of 6 and 18, in the city of Belo Horizonte, MG. Data: weight, height, BP, skinfold thickness, waist circumference, physical activity, total cholesterol (TC), LDL-c, HDL-c, and dietary habits. RESULTSThe prevalence rates for overweight and obesity were 8.4% and 3.1%, respectively. In relation to the students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
20

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 21 publications
1
29
0
20
Order By: Relevance
“…One limitation pointed out by Luukkaa et al 14 is that BMI does not discriminate lean mass from fat mass, and does not permit the separation of subjects with increased muscle mass from those with increased fat mass. However, even the low quartile (Q1) of the distribution of subscapular skinfold, when compared to upper quartile (Q4) is related to increased risk of elevated total cholesterol (TC) levels in children and adolescents 15 . Currently, it is important to know not just the fat mass, but also the fat distribution.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation pointed out by Luukkaa et al 14 is that BMI does not discriminate lean mass from fat mass, and does not permit the separation of subjects with increased muscle mass from those with increased fat mass. However, even the low quartile (Q1) of the distribution of subscapular skinfold, when compared to upper quartile (Q4) is related to increased risk of elevated total cholesterol (TC) levels in children and adolescents 15 . Currently, it is important to know not just the fat mass, but also the fat distribution.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid intra-class correlation (24) , a design effect was calculated to be 2?069 for the sedentary lifestyle variable in a previous study (23) . Therefore, each sample group needed to have 403 3 2?069 5 834 children.…”
Section: Samplementioning
confidence: 99%
“…High-Density Lipoprotein-cholesterol was not inversely associated with BMI adjusted for gender, indicating that adolescents with high BMI have low levels of HDL-c. Other studies done in Brazil 8,15 and elsewhere 13,26 also found an inverse association between HDL-c and overweight or obesity. Since HDL-c is antiatherogenic, low levels predispose to cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 60%
“…Similar results were reported elsewhere 9,14 suggesting that excess weight during adolescence may be associated with undesirable total cholesterol levels. On the other hand, other studies have not found an association between BMI and cholesterol in adolescents 15,25 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation